Nickel allergy and allergic contact dermatitis: A clinical review of immunology, epidemiology, exposure, and treatment - Ahlström, Malin G.; Thyssen, Jacob P.; Wennervaldt, Michael; Menné, Torkil; Johansen, Jeanne D. (Contact dermatitis, 2019)
Nickel is the most frequent cause of contact allergy worldwide and has been studied extensively. This clinical review provides an updated overview of the epidemiology, exposure sources, methods for exposure quantification, skin deposition and penetration, immunology, diagnosis, thresholds for sensitization and elicitation, clinical pictures, prevention, and treatment. The implementation of a nickel regulation in Europe led to a decrease in the prevalence of nickel allergy, and changes in the clinical picture and disease severity. Nevertheless, the prevalences of nickel allergy in the European general population are approximately 8% to 19% in adults and 8% to 10% in children and adolescents, with a strong female predominance. Well‐known consumer items such as jewellery and metal in clothing are still the main causes of nickel allergy and dermatitis, although a wide range of items for both private and occupational use may cause dermatitis. Allergic nickel dermatitis may be localized to the nickel exposure site, be more widespread, or present as hand eczema. Today, efficient methods for exposure quantification exist, and new insights regarding associated risk factors and immunological mechanisms underlying the disease have been obtained. Nevertheless, questions remain in relation to the pathogenesis, the persistent high prevalence, and the treatment of severe cases.